2003
DOI: 10.1046/j.1540-8167.2003.03068.x
|View full text |Cite
|
Sign up to set email alerts
|

Global Right Atrial Mapping Delineates Double Posterior Lines of Block in Patients with Typical Atrial Flutter:

Abstract: Double lines of block were frequently observed in patients with AFL, and both lines may form the posterior boundaries of the AFL circuit. Block was fixed in the lower part of the CT and was functional in the upper part of the CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…When there were 2 block lines, we considered that the anterior line corresponded to the CT and the posterior one to the sinus venosa, based on previous studies. 7,8 It has been reported that a transverse conduction gap in the CT occurs particularly in patients with atrial fibrillation, 19 and in the present study a transverse conduction gap in the CT was observed in 16 of 19 patients with atrial fibrillation. However, there was also a history of atrial fibrillation in 3 of 4 patients with a single complete block.…”
Section: Conduction Patterns In Characteristic Posterolateral Block Dsupporting
confidence: 61%
See 2 more Smart Citations
“…When there were 2 block lines, we considered that the anterior line corresponded to the CT and the posterior one to the sinus venosa, based on previous studies. 7,8 It has been reported that a transverse conduction gap in the CT occurs particularly in patients with atrial fibrillation, 19 and in the present study a transverse conduction gap in the CT was observed in 16 of 19 patients with atrial fibrillation. However, there was also a history of atrial fibrillation in 3 of 4 patients with a single complete block.…”
Section: Conduction Patterns In Characteristic Posterolateral Block Dsupporting
confidence: 61%
“…5,6 However, it has been shown recently that blocking does not occur in that entire region. 7,8 Thus, there may be the complication of another loop reentry, together with typical AFL rotation around the TA. Furthermore, the other loop reentry would travel across the line between the SVC and IVC in the posterolateral wall of the RA, and this has been confirmed by conventional electrophysiological methods, 9 electroanatomic mapping 10 and, recently, by noncontact mapping.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has recently been suggested that transverse conduction block at the CT is not always consistent in some kinds of AFL because the electrical conduction penetrates the CT during AFL in such cases (Cheng et al 1999;Tai et al 2002). Functional barriers have also been noted at the sinus venosa region, which is located in the posteromedial RA, and the Eustachian ridge, which is located near the inferior septal RA, during AFL, regardless of the presence or absence of conduction block in the CT (Chen et al 2003a;Tai et al 2004;Huang et al 2006).…”
Section: Study Populationmentioning
confidence: 99%
“…Recently, it was suggested that two zones of slow conduction existed in the septal part of the isthmus between the IVC and TA and in the lateral wall of the AFL circuit (Hassankhani et al 2003). Further, both the medial isthmus and inferior septal wall have been demonstrated to be areas of slow conduction (Chen et al 2003a). However, there has been some controversy as to the exact location of the area of slow conduction within the AFL circuit.…”
Section: Study Populationmentioning
confidence: 99%